Understanding Islamic Aqidah Through the Lens of Religious Studies in Education: A Literature Analysis of Its Influence and Implications - Siregar, Kardina Engelina (Proceedings of International Conference on Muslim Society and Thought, 2024)
Understanding Islamic aqidah plays an important role in shaping the identity and values of Muslims, especially in the educational context. This research aims to explore the influence of religious studies in deepening understanding of Islamic faith and its implications in the educational context. Through careful analysis of the literature, we investigate how the study of religion can be an enriching lens for understanding Islamic creeds. Our findings reveal that the study of religion not only provides an understanding of the theological aspects of aqidah, but also provides insight into the history, culture, and social context that shapes that understanding. The implication of this research is the development of a holistic educational approach, enabling students to integrate knowledge about Islamic creeds with a broader understanding of religion in general. By emphasizing the values of tolerance, respect for diversity, and intellectual criticism, education based on religious studies can prepare students to face the challenges of the modern world with strong beliefs and a deep understanding of Islamic beliefs. Thus, this research makes an important contribution in enriching discussions about Islamic education that is inclusive and relevant to the times.